Chemical and biological assessment of sediments and water of Khalid Khor, Sharjah, United Arab Emirates. Issue 1 (15th October 2016) - Samara, Fatin; Elsayed, Yehya; Soghomonian, Balik; Knuteson, Sandra L.
Abstract: Water and sediments were collected on March 2013 and April 2014 from Khalid Khor creek area in United Arab Emirates to assess their quality parameters. The pH and alkalinity of the water samples were measured and their values were similar to those of shallow saltwater ecosystems. In addition, elemental analyses and organic compounds were done using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) and Gas Chromatography—Mass Spectroscopy (GC–MS), respectively. The concentration of heavy and trace metals in the water samples were within the acceptable limits except for lead which showed high values, while the concentrations of metals in the sediment samples were relatively high and ranged from 6517 to 13, 768 mg/kg. GC–MS analysis showed the presence of polyaromatic heterocyclic (PAHs) compounds in sediments near the shipping area and in amounts classified as highly carcinogenic; however, no polychlorinated biphenyls (PCB) were identified. Moreover, fecal bacterial contamination in water was detected in concentrations that range between 300 and 10, 140 organisms/100 mL. Highlights: Water and sediment quality was reported for Khalid Khor creek in UAE. Bacterial analysis was high indicating fecal contamination. DO levels in some sites were too low, due to temperature changes to support fish growth. Pb, Fe, Se and Cu were present at high concentrations in water and sediments. Four probable human carcinogenic PAHs were reported in one site.